Frequency and Usefulness in Practicing English Outside Classroom towards Speaking Anxiety in English Education Students - Prakosa, Satria Yudha; Anwar, Khoirul (Jurnal Pendidikan dan Konseling (JPDK), 2022)
There are still many gaps or problems that occured in students’ Speaking English learning activities, especially in activities for learning outside the classroom. In this case, the researcher is interested in exploring the relationship between the frequency and usefulness of students who studied English outside the class room on their level of anxiety. There are still not many researchers who pay attention to this field. In this study, researchers used descriptive quantitative methods to draw correlations between these aspects that influence each other. The type of the instruments that used in this research were FLCAS (Foreign Language Class Anxiety Scale) questionnaire and the Frequency & Usefulness of the Out-of-class Activities. The results show that the average frequency of learning to speak English outside the classroom is 3, while the average value of learning to speak English outside the classroom is 3.31. On the other side, the anxiety value is indicated by the total number of students having a moderate anxiety level of 42.5%. The significance of correlation of the frequency and usefulness of students that studying outside class hours on the level of students’ speaking anxiety is not very significant. Although, these three aspects have a fairly good value. This research is still limited to a quantitative design. Future research is expected to be able to continue with a different design in order to gain new results.